EAEU Transport Policy and Single Transport Space - A. M. Novozhilov (Путеводитель предпринимателя, 2020)
In 2014, the Eurasian Economic Union was created. The states of the Eurasian Economic Union have a unique geographical and geo-economic position, high transit potential. Transport systems in the space of the EAEU member states can ensure the functioning of reliable intercontinental transport communications between the countries of Europe and Asia. Activities are underway to implement a coordinated transport policy of the EAEU member states. The development policy of the transport sector of the economies of the member states of the Eurasian Economic Union is based on the use of the existing integration potential, the synergistic effect of the joint use of rail, road air and water transport.